Efficacy and Safety of Adding Antiangiogenic Therapy to EGFR-Tyrosine Kinase Inhibitors versus EGFR-Tyrosine Kinase Inhibitor Monotherapy in EGFR-Mutant Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis of Randomised Controlled Trials - Hermis Arsena; Sri Melati Munir (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background. Resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) limits the durability of targeted therapy in EGFR-mutant non-small cell lung cancer (NSCLC). Inhibiting the vascular endothelial growth factor (VEGF) axis has been proposed to delay this resistance, but individual trials diverge and the antiangiogenic class has not been synthesised together across treatment settings. This study quantified the effect of adding antiangiogenic therapy to an EGFR-TKI on progression-free survival (PFS) and toxicity. Methods. Four databases were searched for randomised controlled trials (RCTs) comparing an EGFR-TKI plus an antiangiogenic agent (bevacizumab or ramucirumab) with the same EGFR-TKI alone in EGFR-mutant NSCLC. The pre-specified primary analysis was PFS in the first-line setting, expressed as the hazard ratio (HR) and pooled with an inverse-variance random-effects (DerSimonian-Laird) model; a restricted maximum-likelihood model confirmed it. Heterogeneity used I², τ² and a 95% prediction interval; risk of bias used Cochrane RoB 2.0. Results. Seven RCTs (eight reports; 1,512 patients; six first-line, one second-line) were included. In the six first-line trials the combination prolonged PFS (pooled HR 0.61, 95% CI 0.53-0.70; p<0.0001) with no heterogeneity (I²=0%; prediction interval 0.50-0.74); the restricted maximum-likelihood estimate was identical. The benefit was consistent for bevacizumab (HR 0.62, 0.52-0.73) and ramucirumab (HR 0.59, 0.46-0.76), a mean prolongation of median PFS of about 5.5 months. Adding the second-line osimertinib/T790M trial attenuated the effect (HR 0.66, 0.56-0.77; I²=32%), driven by absence of benefit in that setting (HR 0.96). Leave-one-out estimates were stable (0.59-0.63); the Egger test was non-significant. Grade ≥3 adverse events were increased (risk ratio 1.95, 1.47-2.57; absolute increase about 29 percentage points; number needed to harm about 4). Conclusion. Adding antiangiogenic therapy to a first-line EGFR-TKI consistently prolongs PFS in EGFR-mutant NSCLC as a VEGF-pathway class effect, at the cost of roughly doubled severe toxicity and without a demonstrated overall-survival gain. The benefit was not evident in the second-line osimertinib/T790M setting, suggesting the strategy delays rather than overcomes resistance.